2016
DOI: 10.1002/jso.24137
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 64 sarcoma patients referred to a sarcoma center after unplanned excision

Abstract: Patients referred after unplanned excision often have small superficial tumors and the majority fall outside of defined referral criteria. Referral criteria are not a guarantee for detection of all sarcomas and surgeons should always be aware of the possibility of malignancy when removing a tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
3
12
0
2
Order By: Relevance
“…STS from our cohort undergoing UE had been small and were preferably located clearly visible in the subcutis. Similar observations have been made by other investigators 3,6,12. Interestingly, the quality of symptoms did not significantly alter the rate of inadvertent resections, albeit patients reporting a long history of complaints were more likely to undergo UE.…”
Section: Discussionsupporting
confidence: 88%
“…STS from our cohort undergoing UE had been small and were preferably located clearly visible in the subcutis. Similar observations have been made by other investigators 3,6,12. Interestingly, the quality of symptoms did not significantly alter the rate of inadvertent resections, albeit patients reporting a long history of complaints were more likely to undergo UE.…”
Section: Discussionsupporting
confidence: 88%
“…We noticed an improvement in referral to reference centers over time, from 24.2% of patients in 2010 to 55.6% in 2016. Many sarcoma specialists already warned physicians of the pitfalls of delayed referral, assessing the diagnostic pattern of patients regarding their first symptoms [2,8,[19][20][21][22][23][24]. The implementation of an expert network was one of the strategies proposed to improve efficient referral, avoid misdiagnosis, and organize a straightforward sequence of care.…”
Section: Discussionmentioning
confidence: 99%
“…Although avoiding unplanned excisions from occurring altogether is not feasible, we propose a twofold approach to prevent the increased morbidity in high‐grade tumors: (a) preoperative identification of tumors based on the clinical history and radiographic appearance and (b) multimodality therapy in the neoadjuvant and adjuvant setting after UE has occurred. Previous groups have reported that more than one‐third of patients with sarcomas who have undergone UE had the presence of “alarm” symptoms before the surgery which may have warranted referral or further diagnostic imaging before surgery . Further, radiographic appearance on ultrasound may demonstrate suspicious features even in small lesions, and core‐needle biopsy has been demonstrated to identify the grade and histological subtype of STS .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a large multi-institutional cohort of patients was utilized to create a propensity score weighted cohort of patients to circumvent these strongly prognostic tumor characteristics, to assess the reported that more than one-third of patients with sarcomas who have undergone UE had the presence of "alarm" symptoms before the surgery which may have warranted referral or further diagnostic imaging before surgery. 25 Further, radiographic appearance on ultrasound may demonstrate suspicious features even in small lesions, and core-needle biopsy has been demonstrated to identify the grade and histological subtype of STS. [26][27][28][29] In the present study, all patients were treated at tertiary or quaternary referral centers after UE with multidisciplinary specialists in the treatment of STS.…”
Section: Discussionmentioning
confidence: 99%